Polacy we współczesnym życiu diasporalnym - Chodubski, Andrzej (Polityka i Społeczeństwo, 2021)
The article is an attempt to produce an original insight into the functioning of the Polish milieus abroad. It presents an attempt at assessing the current position of the Polish diaspora; its organizational potential; cultural activities; the role of contemporary migration processess as well as the changing position of the Catholic Church. Because of the vast scope of the analytical field, the Author chooses to focus on selected aspects of the diaspora life – those that are, in his opinion, the most important nowadays.